Atomic-resolution dynamics on the surface of amyloid-β protofibrils probed by solution NMR - Fawzi, Nicolas L.; Ying, Jinfa; Ghirlando, Rodolfo; Torchia, Dennis A.; Clore, G. Marius (Nature (London), 2011)
Visibility cloak for hidden proteins When proteins associate with larger structures such as polymers, membranes or solid supports, they usually become 'invisible' to the techniques used to visualize them as free molecules in solution. Marius Clore and colleagues have now developed a new technique of solution nuclear magnetic resonance that can probe such exchange phenomena at atomic resolution. Termed dark-state exchange saturation transfer (DEST), the procedure is demonstrated here by following the aggregation of the amyloid-β monomers implicated in Alzheimer's disease. It should also be adaptable to many of the supramolecular systems encountered in biological systems and materials science. Exchange dynamics between molecules free in solution and bound to the surface of a large supramolecular structure, a polymer, a membrane or solid support are important in many phenomena in biology and materials science. Here we present a novel and generally applicable solution NMR technique, known as dark-state exchange saturation transfer (DEST), to probe such exchange phenomena with atomic resolution. This is illustrated by the exchange reaction between amyloid-β (Aβ) monomers and polydisperse, NMR-invisible (‘dark’) protofibrils, a process of significant interest because the accumulation of toxic, aggregated forms of Aβ, from small oligomers to very large assemblies, has been implicated in the aetiology of Alzheimer’s disease 1 , 2 , 3 , 4 , 5 , 6 . The 15 N-DEST experiment imprints with single-residue-resolution dynamic information on the protofibril-bound species in the form of 15 N transverse relaxation rates ( 15 N- R 2 ) and exchange kinetics between monomers and protofibrils onto the easily observed two-dimensional 1 H– 15 N correlation spectrum of the monomer. The exchanging species on the protofibril surface comprise an ensemble of sparsely populated states where each residue is either tethered to (through other residues) or in direct contact with the surface. The first eight residues exist predominantly in a mobile tethered state, whereas the largely hydrophobic central region and part of the carboxy (C)-terminal hydrophobic region are in direct contact with the protofibril surface for a significant proportion of the time. The C-terminal residues of both Aβ40 and Aβ42 display lower affinity for the protofibril surface, indicating that they are likely to be surface exposed rather than buried as in structures of Aβ fibrils 7 , 8 , 9 , 10 , and might therefore comprise the critical nucleus for fibril formation 11 , 12 . The values, however, are significantly larger for the C-terminal residues of Aβ42 than Aβ40, which might explain the former’s higher propensity for rapid aggregation and fibril formation 13 , 14 .